A spatio-temporal atlas of neonatal diffusion MRI based on kernel ridge regression - Shen, K.; Fripp, J.; Pannek, K.; George, J.; Colditz, P.; Boyd, Roslyn; Rose, S. (2017)
© 2017 IEEE. Spatio-temporal atlas is a useful tool in imaging studies of neurodevelopment, which characterizes the growth of brain, and allows the monitoring of its development. The imaging of preterm and term born infants provides opportunities to develop a series of spatio-temporal atlases that track the changes during the particular period of neurodevelopment between. The aim of this paper is to develop a spatio-temporal atlas of diffusion MRI for neonatal brains between 32 to 42 weeks postmenstrual age (PMA). We subdivided the cohort consisting of preterm- and term-born infants according to their PMA at the MRI scan based on a kernel ridge regression, and generated the atlases based on Fibre Orientation Distribution (FOD) reconstruction of the diffusion data.